Biocatalytic dynamic reductive kinetic resolution of aryl α-chloro β-keto esters: divergent, stereocontrolled synthesis of diltiazem, clentiazem, and siratiazem. Issue 64 (22nd July 2022) - Yue, Xiaoping; Li, Yitong; Liu, Minjie; Sang, Di; Huang, Zedu; Chen, Fener
Abstract : A ketoreductase (KRED)-catalyzed dynamic reductive kinetic resolution strategy was developed for the highly stereoselective and green synthesis of anti -aryl α-chloro β-hydroxy esters. Abstract : The first systematic study of ketoreductase (KRED)-catalyzed dynamic reductive kinetic resolution (DYRKR) on aryl α-chloro β-keto esters was performed, and 15 structurally diverse chiral anti -aryl α-chloro β-hydroxy esters were synthesized in 74–98% isolated yields, along with moderate-to-excellent diastereoselectivity (up to >99 : 1 dr) and good-to-excellent enantioselectivity (mostly >99% ee). LfSDR1-catalyzed complete reduction of 100 g L −1 of substrate 6b at a ten-gram scale was achieved with a continuous fed-batch strategy, affording anti -(2 S, 3 S )-1b, the key intermediate of diltiazem, in a record-breaking space-time yield of 96 g L −1 d −1 . An eight-step synthesis of diltiazem, clentiazem, and siratiazem was accomplished in 32–45% overall yields, featuring this versatile biocatalytic reduction reaction as well as an efficient, green chlorination reaction in flow.